Application of fuzzy delphi technique to identify the elements for designing and developing the e-PBM PI-Poli module - Ahmad Fkrudin Mohamed Yusoff (Tanjung Malim, 2021)
Application of fuzzy delphi technique to identify the elements for designing and developing the e-PBM PI-Poli module by Ahmad Fkrudin Mohamed Yusoff